Correlation Between Visual Improvement and Behavior Change of Municipal Solid Waste Management in Jodipan and Ksatrian Village, Indonesia - Sarli, Prasanti Widyasih; Zakiyya, Nida Maisa; Soewondo, Prayatni (IPTEK Journal of Proceedings Series, 2017)
Indonesia, as a developing country, has many slum areas. Over the years, there have been many projects specifically targeting the improvement of slum areas, both at a national or regional level. One example of such project can be observed in Malang City, East Java, where visual improvements of a slum area is attempted by the application of colorfull paints throughout the settlements. Two of the initial projects are Jodipan and Ksatrian Village that are located on the riverside area of Brantas River, one of the biggest river in East Java. The original idea firstly came to Jodipan Village to improve the cleanliness of the area. As the Jodipan Village improved, this village became a local tourism area. Due to its success, the painting project was then adopted to the Ksatrian Village across the river. Before the project, the residents of the villages were used to throw their municipal solid waste to the river. Since the improvement projects ran, it has been found that the improvement can be linked to residents’ awareness for municipal solid waste management. This study focuses on the correlation of visual improvement and behavior change of municipal solid waste; and the differences between the correlations in each village (Jodipan and Ksatrian). A descriptive model was done by observation and questionnaire to the 48 residents of Jodipan Village and 69 residents of Ksatrian Village, with a tolerance for error of 0,1 and confidence level of 90%.